Fingernail onychomycosis caused by Microsporum canis in a teenager - Pichaya Limphoka (2022)
A healthy 15-year-old girl presented with a total dystrophic nail plate and subungual hyperkeratosis over her left 3rd fingernail. Her 2-year-old shorthair cat had circular erythematous patches of alopecia on the left aspect of its forehead. Fungal culture from the affected nail and her cat both grew Microsporum canis. The girl was treated with terbinafine with clinical and mycological cure.